Iron-silicon magnetic powder core, preparation method and application thereof

CN120636996BActive Publication Date: 2026-11-03HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511003417.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-21
Publication Date
2026-11-03
Estimated Expiration
2045-07-21

AI Technical Summary

Technical Problem

In existing technologies, the preparation of magnetic powder cores using sheet-like alloy particles suffers from difficulties in pressing and molding, low magnetic permeability, and high losses.

Method used

Iron-silicon magnetic powder cores are prepared by heat treatment, passivation, and insulating coating of sheet-like and spherical iron-silicon magnetic powders, followed by pressing and molding in a constant magnetic field and annealing under mold rotation.

Benefits of technology

It enables pressing and molding to be completed in a shorter time, reduces production time, improves magnetic permeability and reduces losses, and optimizes magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005509596260000122
    Figure BDA0005509596260000122
  • Figure BDA0005509596260000131
    Figure BDA0005509596260000131
Patent Text Reader

Abstract

The application belongs to the technical field of magnetic powder core materials, and particularly relates to a Fe-Si magnetic powder core, a preparation method thereof and application thereof. The preparation method comprises the following steps: subjecting flaky Fe-Si magnetic powder and spherical Fe-Si magnetic powder to heat treatment, passivation and insulating coating respectively to obtain product A and product B; mixing the product A and the product B to obtain a mixture; and subjecting the mixture to compression molding and annealing to obtain the Fe-Si magnetic powder core. The flaky Fe-Si magnetic powder has a median size of 80-400 mu m in a plane direction and a median size of 0.01-1 mu m in a thickness direction. The spherical Fe-Si magnetic powder has a median particle size of 3-10 mu m. The mass ratio of the product A to the product B is (6-9):(1-4). The compression molding of the mixture is performed in a constant magnetic field, and a compression molding mold rotates around a geometric center axis thereof. The preparation method has high production efficiency, and the prepared Fe-Si magnetic powder core has excellent magnetic permeability and low loss.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of magnetic powder core technology, specifically relating to an iron-silicon magnetic powder core, its preparation method, and its application. Background Technology

[0002] Magnetic powder cores are trending towards miniaturization, intelligence, high integration, and low loss. Currently, there are mainly pure iron magnetic powder cores and iron alloy magnetic powder cores. Pure iron magnetic powder cores have high saturation magnetic induction intensity but low resistivity, and are usually used in the low-frequency range, with high losses at high frequencies. Currently, the main iron alloy magnetic powder cores used are iron-silicon magnetic powder cores. Although iron alloy magnetic powder cores are lower in cost, have high DC superposition performance, and low loss compared to pure iron magnetic powder cores, their high-frequency losses are still relatively high. Furthermore, iron-silicon magnetic powder cores have low permeability, high losses, and significant heat generation, which is detrimental to the energy efficiency and high performance of devices.

[0003] Existing technology uses sheet-like alloy particles to prepare magnetic powder cores. The sheet-like particles are all arranged in a parallel and orderly manner along the plane of the magnetic ring, which can improve the magnetic permeability and reduce the loss to a certain extent. However, the sheet-like structure is difficult to press and form, and the pressing process may cause the insulation layer to break, thereby increasing the loss. Summary of the Invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the difficulties in pressing and molding existing magnetic powder cores prepared by alloy particles with sheet-like structures, and the defects of low magnetic permeability and high loss of the magnetic powder cores obtained therefrom. Thus, the present invention provides an iron-silicon magnetic powder core, its preparation method and application.

[0005] Therefore, the present invention provides the following technical solution:

[0006] The first aspect of this invention protects a method for preparing an iron-silicon magnetic powder core, wherein the preparation method includes the following steps:

[0007] Flake-shaped iron-silicon magnetic powder and spherical iron-silicon magnetic powder were heat-treated, passivated, and coated with insulation to obtain product A and product B, respectively.

[0008] Product A and product B are mixed to obtain a mixture, which is then pressed into shape and annealed to obtain an iron-silicon magnetic powder core.

[0009] The median size of the sheet-like iron-silicon magnetic powder in the planar direction is 80-400 μm, and the median size in the thickness direction is 0.01-1 μm.

[0010] The median particle size of the spherical iron-silicon magnetic powder is 3-10 μm;

[0011] The mass ratio of product A to product B is (6-9):(1-4);

[0012] The mixture is pressed and molded in a constant magnetic field, and the pressing and molding die rotates about its own geometric central axis.

[0013] In this invention, a magnetic field is applied throughout the pressing process. Typically, but not specifically, when the pressing mold is a magnetic ring, the direction of the magnetic field is parallel to the plane of the magnetic ring mold when it starts to rotate, and the mold rotates around its own geometric central axis.

[0014] In this invention, the median size and median particle size of the planar and thickness directions of the flake-shaped iron-silicon magnetic powder are tested by laser diffraction.

[0015] In this invention, the heat treatment is carried out under a normal pressure protective gas atmosphere or a vacuum, and the protective gas atmosphere includes at least one of hydrogen, nitrogen, and argon; typically, but not limited to, the heat treatment is carried out under a normal pressure hydrogen protective atmosphere or a vacuum; after the heat treatment, the temperature is lowered to room temperature and then passivation treatment is performed, and the cooling process is a conventional cooling method in the art, typically, but not limited to, the cooling rate is 20-30℃ / h.

[0016] According to the present invention, the median size of the sheet-like iron-silicon magnetic powder in the planar direction is 200-300 μm, and the median size in the thickness direction is 0.01-0.7 μm.

[0017] According to the present invention, the median particle size of the spherical iron-silicon magnetic powder is 5-8 μm.

[0018] According to the present invention, the mass ratio of product A to product B is (7-8):(2-3).

[0019] According to the present invention, the magnetic induction intensity of the constant magnetic field is 0.1-5T, and the rotation speed of the pressing mold is 20-80r / min.

[0020] According to the present invention, the magnetic induction intensity of the constant magnetic field is 0.3-0.6T, and the rotation speed of the pressing mold is 40-60r / min.

[0021] According to the present invention, the iron content is 93-97 wt% and the silicon content is 3-7 wt% based on the mass of the flake-shaped iron-silicon magnetic powder.

[0022] According to the present invention, the spherical iron-silicon magnetic powder contains 93-97 wt% iron and 3-7 wt% silicon by mass.

[0023] According to the present invention, the conditions for the heat treatment include: a temperature of 650-800°C and a time of 2-3 hours.

[0024] According to the present invention, the passivation includes: mixing heat-treated sheet-like iron-silicon magnetic powder and spherical iron-silicon magnetic powder with a passivating agent and a first solvent, respectively, and then drying.

[0025] According to the present invention, the amount of the passivating agent is 0.1-1 wt% based on the mass of the flake-shaped iron-silicon magnetic powder.

[0026] According to the present invention, the amount of the passivating agent is 0.1-1 wt% based on the mass of the spherical iron-silicon magnetic powder.

[0027] According to the present invention, the insulating coating includes: mixing passivated flake iron-silicon magnetic powder and spherical iron-silicon magnetic powder with modified insulating adhesive liquid and a second solvent, respectively, drying, crushing, and sieving.

[0028] According to the present invention, the modified insulating adhesive comprises silica sol, silane coupling agent and polyurethane.

[0029] According to the present invention, the mass ratio of the silica sol, silane coupling agent and polyurethane is (60-70):1:(30-40).

[0030] According to the present invention, the amount of the modified insulating adhesive solution is 1-2 wt% based on the mass of the flake-shaped iron-silicon magnetic powder.

[0031] According to the present invention, the amount of the modified insulating adhesive liquid is 1-2 wt% based on the mass of the spherical iron-silicon magnetic powder.

[0032] According to the present invention, the mixture is also mixed with a release agent before compression molding.

[0033] According to the present invention, the amount of the release agent is 0.2-0.6 wt% based on the mass of the mixture.

[0034] According to the present invention, the conditions for compression molding include: pressure of 1500-2000 MPa and time of 1-10 s; optionally, the time is 1-7 s.

[0035] According to the present invention, the annealing conditions include: a temperature of 680-720°C and a time of 1-2 hours.

[0036] In this invention, the passivating agent is a conventional passivating agent in the art, typically, without limitation, including phosphoric acid and / or aluminum dihydrogen phosphate; the first solvent is a conventional solvent in the art, typically, without limitation, including at least one of water (deionized water), acetone, and ethanol, the amount of the first solvent is not limited, as long as it can completely submerge the material, and the passivation time is 5-30 minutes; the drying is a conventional drying method in the art, the drying method and specific conditions are not limited, as long as it can dry completely, typically, without limitation, including at least one of natural drying, heated drying, and reduced pressure drying.

[0037] In this invention, the second solvent is a conventional solvent in the art, and the second solvent has good miscibility with the modified insulating adhesive liquid. Typically, without limitation, the second solvent includes acetone and / or ethanol, and the amount of the second solvent is not limited, as long as it can completely submerge the material. The drying is a conventional drying method in the art, and the drying method and specific conditions are not limited, as long as it can dry completely. Typically, without limitation, the drying includes at least one of natural drying, heated drying, and reduced pressure drying.

[0038] In this invention, the release agent is a conventional release agent in the art, typically and non-limitingly, comprising stearates, optionally including zinc stearate.

[0039] In this invention, the annealing is conventional annealing in the art. Typically, without limitation, the annealing is carried out under nitrogen or inert gas protection, and after annealing, the furnace is cooled to room temperature to obtain an iron-silicon magnetic powder core.

[0040] A second aspect of this invention protects an iron-silicon magnetic powder core, wherein the iron-silicon magnetic powder core is prepared by the aforementioned preparation method.

[0041] The third aspect of this invention protects the application of the aforementioned iron-silicon magnetic powder core in any one of the fields of new energy, electrical engineering, and communication.

[0042] In this invention, the new energy field includes the new energy vehicle industry.

[0043] The technical solution of this invention has the following advantages:

[0044] 1. The present invention provides a method for preparing an iron-silicon magnetic powder core, the method comprising the following steps: heat-treating, passivating, and insulatingly coating sheet-like iron-silicon magnetic powder and spherical iron-silicon magnetic powder respectively to obtain product A and product B; mixing product A and product B to obtain a mixture; pressing the mixture into shape and annealing to obtain an iron-silicon magnetic powder core; wherein, the median size in the planar direction of the sheet-like iron-silicon magnetic powder is 80-400 μm, and the median size in the thickness direction is 0.01-1 μm; the median particle size of the spherical iron-silicon magnetic powder is 3-10 μm; the mass ratio of product A to product B is (6-9):(1-4); the pressing of the mixture is carried out in a constant magnetic field, and the pressing mold rotates around its own geometric center axis; the pressing of the preparation method of the present invention can be completed in a short time without the insulation layer breaking under high pressure, thus reducing the production period and improving production efficiency; the obtained iron-silicon magnetic powder core has excellent magnetic permeability and low loss. Specifically, sheet-like iron-silicon magnetic powder of a certain size is easily oriented in a magnetic field, forming a structure in which the magnetic domain alignment direction is consistent with the pressing direction, thereby improving magnetic permeability. Meanwhile, spherical iron-silicon magnetic powder of a certain size provides uniform filling and coating, helping to reduce core loss. The graded dosage achieves tight particle filling, reducing pressing conditions and material waste. Simultaneously, the use of a rotating pressing die under a constant magnetic field promotes the directional alignment of the iron-silicon magnetic powder, optimizing the magnetic domain structure. This improves preparation efficiency while enhancing magnetic permeability and suppressing losses, resulting in excellent magnetic properties.

[0045] 2. The method for preparing iron-silicon magnetic powder cores provided by the present invention further limits the size of sheet-like iron-silicon powder, the size of spherical iron-silicon powder, and the mass ratio of product A to product B, which can further optimize the arrangement structure of iron-silicon powder, reduce the requirements for pressing and molding conditions, and improve magnetic properties.

[0046] 3. The method for preparing iron-silicon magnetic powder cores provided by the present invention further limits the magnetic field conditions, which can further reduce friction and energy loss during pressing and molding, reduce waste, and further promote the directional arrangement of iron-silicon magnetic powder, adjust the magnetic domain arrangement direction, and improve magnetic properties. Detailed Implementation

[0047] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.

[0048] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0049] Silica sol: Jiangsu Guolian Technology Co., Ltd., grade CH83-120C;

[0050] Silane coupling agent: Yoshida Chemical, brand name KH-560;

[0051] Polyurethane: Hefei Anke, grade PU303;

[0052] The outer diameter of the compression molding die is 12.7 mm, the inner diameter is 7.6 mm, and the height is 3 mm.

[0053] Example 1

[0054] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0055] (1) Selection of magnetic powder

[0056] The median size of the planar direction of the flake iron-silicon magnetic powder is 200 μm, and the median size of the thickness direction is 0.05 μm. Based on the mass of the flake iron-silicon magnetic powder, the mass percentage of iron is 95.5 wt% and the mass percentage of silicon is 4.5 wt%.

[0057] The median particle size of the spherical iron-silicon magnetic powder is 5 μm. Based on the mass of the spherical iron-silicon magnetic powder, the mass percentage of iron is 95.5 wt% and the mass percentage of silicon is 4.5 wt%.

[0058] (2) Heat treatment

[0059] The sheet-like iron-silicon magnetic powder and the spherical iron-silicon magnetic powder from step (1) are placed into a heat treatment furnace. The atmosphere inside the furnace can be a vacuum. The temperature of the heat treatment furnace is 740℃ and the time is 2h. Then, the temperature is reduced to room temperature at a rate of 30℃ / h before the powder is removed from the furnace.

[0060] (3) Passivation

[0061] The heat-treated flake iron-silicon magnetic powder obtained in step (2) is mixed with phosphoric acid and acetone. The amount of phosphoric acid is 0.2 wt% based on the mass of the flake iron-silicon magnetic powder. During mixing, the acetone completely covers the flake iron-silicon magnetic powder obtained in step (2). The mixing time is 10 min. The powder is then dried at 80°C to obtain passivated flake iron-silicon magnetic powder.

[0062] The heat-treated spherical iron-silicon magnetic powder obtained in step (2) is mixed with phosphoric acid and acetone. The amount of phosphoric acid is 0.2 wt% based on the mass of the spherical iron-silicon magnetic powder. During mixing, the acetone completely covers the spherical iron-silicon magnetic powder obtained in step (2). The mixture is dried at 80°C to obtain passivated spherical iron-silicon magnetic powder.

[0063] (4) Insulation Covering

[0064] The modified insulating adhesive is a mixed solution of silica sol, silane coupling agent, and polyurethane, wherein the mass ratio of silica sol, silane coupling agent, and polyurethane is 60:1:40.

[0065] The passivated flake iron-silicon magnetic powder obtained in step (3) is mixed with modified insulating adhesive and acetone. The amount of modified insulating adhesive is 1.5 wt% based on the mass of the flake iron-silicon magnetic powder. During mixing, the acetone completely covers the passivated flake iron-silicon magnetic powder obtained in step (3). The powder is then dried naturally, crushed, and sieved to obtain product A.

[0066] The passivated spherical iron-silicon magnetic powder obtained in step (3) is mixed with modified insulating adhesive and acetone. The amount of modified insulating adhesive is 1.5 wt% based on the mass of the spherical iron-silicon magnetic powder. During mixing, the acetone completely covers the passivated spherical iron-silicon magnetic powder obtained in step (3). The powder is then dried naturally, crushed, and sieved to obtain product B.

[0067] (5) Magnetic powder gradation mixing

[0068] Product A and product B are mixed in a graded manner to obtain a mixture, wherein the mass ratio of product A to product B is 7:3;

[0069] (6) Compression molding

[0070] The mixture was mixed with zinc stearate, and the amount of zinc stearate was 0.3 wt% based on the mass of the mixture. The mixture was then placed in a press for pressing and molding at a pressure of 1900 MPa for 2 seconds. The pressing and molding was carried out in a magnetic field, which was a constant magnetic field with a magnetic induction intensity of 0.3 T. The pressing and molding die rotated around its own geometric center axis at a rotation speed of 60 r / min.

[0071] (7) Annealing

[0072] The product obtained in step (6) is placed in a furnace for annealing. The annealing is carried out under nitrogen protection at a temperature of 700°C for 1 hour. The product is then cooled to room temperature in the furnace to obtain an iron-silicon magnetic powder core.

[0073] Example 2

[0074] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0075] (1) Selection of magnetic powder

[0076] The median size of the planar direction of the flake iron-silicon magnetic powder is 300 μm, and the median size of the thickness direction is 0.5 μm. Based on the mass of the flake iron-silicon magnetic powder, the mass percentage of iron is 95.5 wt% and the mass percentage of silicon is 4.5 wt%.

[0077] The median particle size of the spherical iron-silicon magnetic powder is 5 μm. Based on the mass of the spherical iron-silicon magnetic powder, the mass percentage of iron is 95.5 wt% and the mass percentage of silicon is 4.5 wt%.

[0078] (2) Heat treatment

[0079] The sheet-like iron-silicon magnetic powder and the spherical iron-silicon magnetic powder from step (1) are placed into a heat treatment furnace. The atmosphere inside the furnace can be a vacuum. The temperature of the heat treatment furnace is 650℃ and the time is 3h. Then, the temperature is reduced to room temperature at a rate of 25℃ / h before the powder is removed from the furnace.

[0080] (3) Passivation

[0081] The heat-treated sheet iron-silicon magnetic powder obtained in step (2) is mixed with aluminum dihydrogen phosphate and ethanol. The amount of aluminum dihydrogen phosphate is 0.8 wt% based on the mass of the sheet iron-silicon magnetic powder. During mixing, the ethanol completely covers the sheet iron-silicon magnetic powder obtained in step (2). The mixing time is 10 min. The powder is dried at 90°C to obtain passivated sheet iron-silicon magnetic powder.

[0082] The heat-treated spherical iron-silicon magnetic powder obtained in step (2) is mixed with aluminum dihydrogen phosphate and ethanol. The amount of aluminum dihydrogen phosphate is 0.8 wt% based on the mass of the spherical iron-silicon magnetic powder. During mixing, the ethanol completely covers the spherical iron-silicon magnetic powder obtained in step (2). The mixture is dried at 90°C to obtain passivated spherical iron-silicon magnetic powder.

[0083] (4) Insulation Covering

[0084] The modified insulating adhesive is a mixed solution of silica sol, silane coupling agent, and polyurethane, wherein the mass ratio of silica sol, silane coupling agent, and polyurethane is 60:1:40.

[0085] The passivated flake iron-silicon magnetic powder obtained in step (3) is mixed with modified insulating adhesive and ethanol. The amount of modified insulating adhesive is 1 wt% based on the mass of the flake iron-silicon magnetic powder. During mixing, the ethanol completely covers the passivated flake iron-silicon magnetic powder obtained in step (3). The powder is then dried naturally, crushed, and sieved to obtain product A.

[0086] The passivated spherical iron-silicon magnetic powder obtained in step (3) is mixed with modified insulating adhesive and ethanol. The amount of modified insulating adhesive is 2 wt% based on the mass of the spherical iron-silicon magnetic powder. During mixing, the ethanol completely covers the passivated spherical iron-silicon magnetic powder obtained in step (3). The powder is then naturally dried, crushed, and sieved to obtain product B.

[0087] (5) Magnetic powder gradation mixing

[0088] Product A and product B are mixed in a graded manner to obtain a mixture, wherein the mass ratio of product A to product B is 7.5:2;

[0089] (6) Compression molding

[0090] The mixture was mixed with sodium stearate, and the amount of sodium stearate was 0.6 wt% based on the mass of the mixture. The mixture was then placed in a press for pressing and molding at a pressure of 1500 MPa for 2 seconds. The pressing and molding was carried out in a magnetic field, which was a constant magnetic field with a magnetic induction intensity of 7 T. The pressing and molding die rotated around its own geometric center axis at a rotation speed of 80 r / min.

[0091] (7) Annealing

[0092] The product obtained in step (6) was placed in a furnace for annealing. The annealing was carried out under nitrogen protection at a temperature of 680°C for 1.5 hours. The product was then cooled to room temperature in the furnace to obtain an iron-silicon magnetic powder core.

[0093] Example 3

[0094] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0095] The difference from Example 1 is that in step (1), the median size of the sheet-like iron-silicon magnetic powder in the planar direction is 400 μm and the median size in the thickness direction is 1 μm.

[0096] Example 4

[0097] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0098] The method is the same as in Example 1, except that in step (1), the median particle size of the spherical iron-silicon magnetic powder is 10 μm.

[0099] Example 5

[0100] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0101] The difference from Example 1 is that in step (5), the mass ratio of product A to product B is 3:2.

[0102] Example 6

[0103] This embodiment provides a method for preparing an iron-silicon magnetic powder core, including the following steps;

[0104] The difference from Example 2 is that in step (6), the pressing and molding is carried out in a magnetic field. The magnetic field is a constant magnetic field with a magnetic induction intensity of 1T. The pressing and molding mold rotates around its own geometric center axis at a speed of 70r / min.

[0105] Comparative Example 1

[0106] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0107] The difference from Example 6 is that in step (1), the median size of the planar direction of the flake iron-silicon magnetic powder is 500 μm, the median size of the thickness direction is 1.2 μm, and the median particle size of the spherical iron-silicon magnetic powder is 15 μm.

[0108] Comparative Example 2

[0109] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0110] The method is the same as in Example 6, except that in step (5), the mass ratio of product A to product B is 5:5.

[0111] Comparative Example 3

[0112] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0113] The difference from Example 1 is that in step (6), the magnetic field is a constant magnetic field with a magnetic induction intensity of 0.3T, and the pressing mold does not rotate.

[0114] Comparative Example 4

[0115] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0116] The difference from Example 1 is that in step (6), no external magnetic field is applied and the pressing mold does not rotate.

[0117] Comparative Example 5

[0118] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0119] The method is the same as in Example 6, except that spherical iron-silicon magnetic powder is not added. That is, in step (1), the spherical iron-silicon magnetic powder is replaced with sheet-like iron-silicon magnetic powder of equal mass.

[0120] Comparative Example 6

[0121] This comparative example provides a method for preparing an iron-silicon magnetic powder core, comprising the following steps;

[0122] The method is the same as in Example 6, except that no flake iron-silicon magnetic powder is added. That is, in step (1), the flake iron-silicon magnetic powder is replaced with spherical iron-silicon magnetic powder of equal mass.

[0123] Test case

[0124] The examples and comparative examples yielded magnetic powder cores with an outer diameter of 12.7 mm, an inner diameter of 7.6 mm, and a height of 3 mm. The specific pressing conditions in step (6) of the examples and comparative examples are shown in Table 1. For the obtained magnetic powder cores, the density ρ of the magnetic powder core was tested using the water displacement method. The core was then wound, and the inductance L was tested using an LCR meter at a frequency of 100 kHz. L is the inductance (H), μ0 is the free permeability (H / m), μ is the effective permeability, N is the number of turns of the coil, and A is the cross-sectional area of ​​the magnetic core (m²). 2 ), l is the magnetic path length (m), calculate the effective permeability μ of the magnetic powder core; use the Japanese Iwasaki SY-8218 soft magnetic BH analyzer to test the AC volume loss Pcv of the magnetic core. Test conditions: frequency 50kHz, magnetic induction intensity 100mT, temperature 25℃.

[0125] The specific test results are shown in Table 1;

[0126] Table 1

[0127]

[0128]

[0129] A comparison of the embodiments and comparative examples shows that the embodiments can use higher pressure and complete the pressing in a shorter time, while comparative examples 1, 2, 5, and 6 can only be pressed for a long time under low pressure in order to avoid the insulation layer from cracking. The present invention reduces the production cycle, improves production efficiency, and the iron-silicon magnetic powder core obtained has excellent magnetic permeability and low loss.

[0130] A comparison of Examples 1, 5, and 6 shows that there is a synergistic effect between flake-shaped and spherical iron-silicon magnetic powders. A comparison of Examples 1 and 1 shows that flake-shaped iron-silicon magnetic powder of a specific size is easily oriented in a magnetic field, forming a structure in which the magnetic domain alignment direction is consistent with the pressing direction, thereby improving the magnetic permeability. Meanwhile, spherical iron-silicon magnetic powder of a specific size provides uniform filling and coating, which helps to reduce core loss. A comparison of Examples 1 and 2 shows that the graded dosage achieves dense particle filling to reduce pressing conditions and reduce raw material waste. A comparison of Examples 1, 4, and 5 shows that further limiting the size of the flake-shaped iron-silicon powder, the size of the spherical iron-silicon powder, and the mass ratio of product A to product B can further optimize the arrangement structure of the iron-silicon powder, reduce the pressing and molding requirements, and improve the magnetic properties.

[0131] A comparison of Examples 1, 3, and 4 shows that although Comparative Examples 3 and 4 can also withstand the corresponding pressure, the pressing time is longer. Furthermore, the use of a rotating pressing mold under a constant magnetic field promotes the directional alignment of iron-silicon magnetic powder, optimizes the magnetic domain structure, and enhances magnetic permeability and suppresses losses while improving preparation efficiency, thereby obtaining excellent magnetic properties. A comparison of Examples 1 and 6 shows that further limiting the magnetic field conditions can further reduce friction and energy loss during pressing, reduce waste, and further promote the directional alignment of iron-silicon magnetic powder, adjust the magnetic domain alignment direction, and improve magnetic properties.

[0132] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing an iron-silicon magnetic powder core, characterized in that, The preparation method includes the following steps: Flake-shaped iron-silicon magnetic powder and spherical iron-silicon magnetic powder were heat-treated, passivated, and coated with insulation to obtain product A and product B, respectively. Product A and product B are mixed to obtain a mixture, which is then pressed into shape and annealed to obtain an iron-silicon magnetic powder core. The median size of the sheet-like iron-silicon magnetic powder in the planar direction is 80-400 μm, and the median size in the thickness direction is 0.01-1 μm. The median particle size of the spherical iron-silicon magnetic powder is 3-10 μm; The mass ratio of product A to product B is (6-9):(1-4); The mixture is pressed and molded in a constant magnetic field, and the pressing and molding die rotates about its own geometric central axis.

2. The preparation method according to claim 1, characterized in that, The median size of the sheet-like iron-silicon magnetic powder in the planar direction is 200-300 μm, and the median size in the thickness direction is 0.01-0.7 μm. And / or, the median particle size of the spherical iron-silicon magnetic powder is 5-8 μm; And / or, the mass ratio of product A to product B is (7-8):(2-3).

3. The preparation method according to claim 1 or 2, characterized in that, The magnetic induction intensity of the constant magnetic field is 0.1-5T, and the rotation speed of the pressing mold is 20-80r / min.

4. The preparation method according to claim 1 or 2, characterized in that, The magnetic induction intensity of the constant magnetic field is 0.3-0.6T, and the rotation speed of the pressing mold is 40-60r / min.

5. The preparation method according to claim 1, characterized in that, Based on the mass of the flake-shaped iron-silicon magnetic powder, the iron content is 93-97 wt% and the silicon content is 3-7 wt%. And / or, based on the mass of the spherical iron-silicon magnetic powder, the iron content is 93-97 wt% and the silicon content is 3-7 wt%.

6. The preparation method according to claim 1, characterized in that, The heat treatment conditions include: a temperature of 650-800℃ and a time of 2-3 hours.

7. The preparation method according to claim 1, characterized in that, The passivation process includes: mixing heat-treated sheet-like iron-silicon magnetic powder and spherical iron-silicon magnetic powder with a passivating agent and a first solvent, respectively, and then drying.

8. The preparation method according to claim 7, characterized in that, The amount of passivating agent used is 0.1-1 wt% based on the mass of the flake iron-silicon magnetic powder.

9. The preparation method according to claim 7, characterized in that, The amount of passivating agent used is 0.1-1 wt% based on the mass of the spherical iron-silicon magnetic powder.

10. The preparation method according to claim 1, characterized in that, The insulating coating process includes: mixing passivated flake iron-silicon magnetic powder and spherical iron-silicon magnetic powder with modified insulating adhesive liquid and a second solvent, respectively, drying, crushing, and sieving.

11. The preparation method according to claim 10, characterized in that, The modified insulating adhesive includes silica sol, silane coupling agent, and polyurethane.

12. The preparation method according to claim 11, characterized in that, The mass ratio of the silica sol, silane coupling agent and polyurethane is (60-70):1:(30-40).

13. The preparation method according to claim 10, characterized in that, The amount of the modified insulating adhesive liquid is 1-2 wt% based on the mass of the flake iron-silicon magnetic powder.

14. The preparation method according to claim 10, characterized in that, The amount of the modified insulating adhesive liquid is 1-2 wt% based on the mass of the spherical iron-silicon magnetic powder.

15. The preparation method according to claim 1, characterized in that, Before compression molding, the mixture is also mixed with a release agent.

16. The preparation method according to claim 15, characterized in that, The amount of the release agent is 0.2-0.6 wt% based on the mass of the mixture.

17. The preparation method according to claim 1, characterized in that, The conditions for compression molding include: pressure of 1500-2000 MPa and time of 1-10 s.

18. The preparation method according to claim 17, characterized in that, The pressing and molding time is 1-7 seconds.

19. The preparation method according to claim 1, characterized in that, The annealing conditions include a temperature of 680-720℃ and a time of 1-2 hours.

20. A type of iron-silicon magnetic powder core, characterized in that, The iron-silicon magnetic powder core is prepared by the preparation method described in any one of claims 1-19.

21. An application of the iron-silicon magnetic powder core as described in claim 20 in any one of new energy, electrical, and communication fields.

Citation Information

Patent Citations

  • Powder based soft magnetic inductive component, and a method and a device for production thereof

    CN101883673A

  • Soft magnetic alloy powder, production method thereof, and dust core using same

    CN110153383A